Physical characterization of coconut fiber (cocos nucifera) and melinjo peel fiber (gnetum gnemon) for potential armor applications - Wahyu Kumala Sari; Muhamad Sofian; Yusniati Andini Putri; Raychanezka Whyatta Pembhayoun Maydjaller Camqliew (Privietlab, 2025)
This study aims to investigate the structural characteristics and mechanical properties of young coconut coir fiber (Cocos nucifera L.) and melinjo seed coat fiber (Gnetum gnemon) as potential raw materials for developing bio-based natural armor derived from local resources. A descriptive method with an experimental laboratory approach was employed, including morphological analysis using scanning electron microscopy (SEM) and tensile strength testing based on the ASTM D3379-02 standards. The results indicate that young coconut coir fibers possess a porous structure with a high lignin content that functions as an energy-absorbing layer, whereas melinjo fibers exhibit parallel fibril orientation and high cellulose content, contributing to tensile strength and structural stiffness. The combination of these two natural fibers demonstrates the potential of a lightweight, durable, and eco-friendly hybrid composite that mimics the protective mechanism of biological armor systems. These findings provide a scientific foundation for the development of protective materials based on local biomaterials and support sustainable innovation in defense material production.